2022
DOI: 10.1037/emo0000755
|View full text |Cite
|
Sign up to set email alerts
|

Getting over it: Working memory capacity and affective responses to stressful events in daily life.

Abstract: Working memory capacity (WMC) refers to the capacity to maintain information in short-term storage while processing other information. WMC has been related to higher-order cognitive functions like language comprehension and goal maintenance, and a growing body of research implicates WMC in emotion processes as well. The current research tested the preregistered hypothesis that individual differences in WMC relate to affective states following daily stressors. We measured WMC in 92 participants using both neutr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 41 publications
(60 reference statements)
0
6
0
Order By: Relevance
“…Empirically, individual differences in attention control explain considerable variance in academic achievement (Ahmed et al, 2019;Blankenship et al, 2019;McVay and Kane, 2012), job performance (Nelson, 2003;Guo et al, 2020;Bosco et al, 2015), emotion regulation (Engen & Anderson, 2018;Garrison & Schmeichel, 2020;Moran, 2016), rationality , sensory discrimination ability (Tsukahara et al, 2020), and complex problem solving (Dempster, 1991;Draheim et al, 2021;Martin et al, 2020;Salthouse et al, 2003). For a review of the expansive role of attention control on complex behavior, see Draheim et al (2022).…”
Section: Attention Control Measures Improve the Prediction Of Perform...mentioning
confidence: 99%
“…Empirically, individual differences in attention control explain considerable variance in academic achievement (Ahmed et al, 2019;Blankenship et al, 2019;McVay and Kane, 2012), job performance (Nelson, 2003;Guo et al, 2020;Bosco et al, 2015), emotion regulation (Engen & Anderson, 2018;Garrison & Schmeichel, 2020;Moran, 2016), rationality , sensory discrimination ability (Tsukahara et al, 2020), and complex problem solving (Dempster, 1991;Draheim et al, 2021;Martin et al, 2020;Salthouse et al, 2003). For a review of the expansive role of attention control on complex behavior, see Draheim et al (2022).…”
Section: Attention Control Measures Improve the Prediction Of Perform...mentioning
confidence: 99%
“…Applied research over the past 30 years has demonstrated that individual differences in WMC are strongly associated with important domains of higher-order cognition, development, and behavior including fluid intelligence/reasoning ability (Conway et al, 2003;Kyllonen & Christal, 1990), control of attention/cognitive control (Engle, 2010;Redick, 2013), mind wandering (McVay & Kane, 2009;Unsworth et al, 2012), and everyday skills such as driving (Wood, Hartley, Furley, & Wilson, 2016). Recent work has also focused attention on the possibility that WMC may index an individual's capacity to carry out goal-directed behavior, modifying how individuals respond in the presence of an environmental/contextual challenge (Hofmann, Gschwendner, Friese, Wiers, & Schmitt, 2008;Hofmann, Schmeichel, & Baddeley, 2012;Garrison & Schmeichel, 2020).…”
Section: Ambulatory Cognitive Assessment Of Wmc In Applied Researchmentioning
confidence: 99%
“…behave more consistently with stated behavioral standards; Hofmann, Friese, & Roefs, 2009;Hofmann, Friese, & Wiers, 2011). In addition, studies linking lab-based assessment of WMC with EMA of stress-related processes indicate that individual differences in WMC may predict negative affective responses to stressor exposures over the course of daily life (Garrison & Schmeichel, 2020). Critically, these examples of work connecting WMC to complex behavioral processes are based on single lab-based assessments of WMC, which has limited examination of the role of WMC in these processes to the level of inter-individual differences.…”
Section: Introductionmentioning
confidence: 96%
“…For example, Eckenrode (1984) recorded participant mood and the presence/absence of negative event/s for 28 consecutive days, and as expected participants reporting more frequent negative events tended to be those with lower mood. More recent investigations have evaluated how various factors can influence mood changes in response to life events, such as personality factors (Leger et al, 2016;Polk et al, 2020;Yang, 2020), genetic factors (Sicorello et al, 2020), perceived neighbourhood characteristics (Scott et al, 2018), working memory capacity (Garrison & Schmeichel, 2020;Pe et al, 2015), cognitive appraisals (Brose et al, 2020;Fosco & Lydon-Staley, 2019;Gunaydin et al, 2016;Panaite et al, 2019), attentional bias (Iijima et al, 2018), having a sense of purpose (Hill et al, 2018), having a sense of control (Koffer et al, 2019), humour (Nezlek et al, 2020), physical activity (Puterman et al, 2017), sexual activity (Kashdan et al, 2018), social behaviour (Schacter & Margolin, 2018), cognitive-behavioural therapy intervention (McIntyre et al, 2019), and various coping strategies (Finkelstein-Fox et al, 2019;Santiago et al, 2016;Shermeyer et al, 2018). For example, Koffer et al (2019) obtained daily reports from 150 adults over 9 weeks and found that individuals with a higher sense of personal control typically were less reactive to negative daily events.…”
Section: Study 3 An Example Of Daily Mood Monitoring Using the Beesmentioning
confidence: 99%